News Framing of the Agreement on Reciprocal Trade Controversy on Kompas.com and Tempo.co - Arrayyan Mafaza Agasta; Roziana Febrianita (CONVERSE Journal Communication Science, 2026)
The signing of the Agreement on Reciprocal Trade (ART) between Indonesia and the United States in early 2026 triggered an economic sovereignty polemic due to a significant asymmetry: 217 obligations for Indonesia versus 6 for the US. This policy was contrastingly constructed by national online news portals. This study aims to compare the news framing of the ART polemic on Tempo.co and Kompas.com. Employing a descriptive qualitative approach with a constructivism paradigm, data were collected through digital documentation of 12 news texts published between February 20 and March 2, 2026. The texts were analyzed using Robert N. Entman’s Framing Analysis and Vincent Mosco’s Political Economy of Communication Theory to trace underlying ideological motives. The results demonstrate an extreme divergence. Representing an independent watchdog ideology, Tempo.co framed ART as a threat of economic neocolonialism due to the loss of digital tax authority. Conversely, Kompas.com, operating under a massive media conglomeration, framed ART optimistically as a savior for investment and export stability to avoid market instability. In conclusion, the reality of international policy news on digital platforms is never neutral; it is absolutely dictated by the ownership structure dynamics and the political economy interests of the press institutions.